The Constitution a title-deed to woman's franchise. A letter to Charles Sumner. - Tilton, Theodore, 1835-1907.; Stone, Lucy, 1818-1893; National American Woman Suffrage Association Collection (Library of Congress) (New York, Pub. at the office of the Golden age, 1871)
This letter to Charles Sumner requests that he use his influence to urge the passage of legislation which would force New York to permit women to vote as guaranteed them by the Fourteenth and Fifteenth Amendments.
Also available in digital form on the Library of Congress Web site.
Keywords: Women -- Suffrage